Analisis Perbandingan Perkembangan Kognitif Siswa SD dan SMP Berdasarkan Teori Piaget selama Pandemi COVID-19 - Muh Asdar; Clara Anugrah Barus (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
AbstractThe COVID-19 pandemic has caused changes in various sectors, including the education sector. As a measure to stop the spread of the virus, Indonesia in March 2020 began implementing an online school policy. However, this change has an impact on the cognitive development of students, especially at the elementary and junior high school levels. The purpose of this review is to analyze cognitive development that refers to Jean Piaget’s theory in elementary and junior high school students during the COVID-19 pandemic. The results of the literature review show that there is a decrease in cognitive development in elementary and junior high school students during online teaching and learning activities. This is related to the cognitive development of elementary school students who are still in the concrete operational phase and junior high school students who are in the formal operational stage, so that online learning activities cannot optimally facilitate the learning activities of elementary and junior high school students. The data shows a number of elementary and junior high school students who do not understand the learning material during the online learning system. Some of the causes include limited use of learning methods, less than optimal two-way communication between teachers and students, and teacher-student interactions that are not optimal. Some things that can be done to optimize the online learning system and improve the cognitive abilities of elementary and junior high school students are the teacher’s role in motivating students through the media and the selection of appropriate learning methods.Abstrak Pandemi COVID-19 menyebabkan perubahan pada berbagai sektor, termasuk pada sektor pendidikan. Sebagai langkah untuk menghentikan penyebaran virus, Indonesia pada Maret 2020 mulai menerapkan kebijakan sekolah daring. Namun perubahaan ini berdampak pada perkembangan kognitif siswa, terutama pada tingkat Sekolah Dasar dan Sekolah Menengah Pertama. Tujuan dari review ini adalah menganalisis perkembangan kognitif yang merujuk pada teori Jean Piaget pada siswa SD dan SMP selama masa pandemi COVID-19. Hasil tinjauan literatur menunjukkan terdapat penurunan perkembangan kognitif pada siswa SD dan SMP selama dilakukan aktivitas belajar-mengajar secara daring. Hal ini berkaitan dengan perkembangan kognitif siswa SD yang masih pada fase operasional konkret dan pada siswa SMP yang berada pada tahapan operasional formal, sehingga aktivitas belajar secara daring tidak bisa secara optimal memfasilitasi aktivitas belajar siswa SD dan SMP. Data menunjukkan sejumlah siswa SD dan SMP yang tidak memahami materi pembelajaran selama pembelajaran sistem online. Beberapa penyebabnya antara lain keterbatasan penggunaan metode pembelajaran, kurang optimalnya komunikasi dua arah antara guru dan siswa, dan interaksi guru dan siswa yang tidak maksimal. Beberapa hal yang dapat dilakukan untuk mengoptimalkan sistem pembelajaran online dan meningkatkan kemampuan kognitif siswa SD dan SMP adalah peran guru dalam memotivasi siswa melalui media dan pemilihan metode pembelajaran yang sesuai.